Studi Komparatif Metode NWC Dan Metode VAM Dalam Optimasi Pengiriman (Penelitian Kasus: PT. Baruna Globalindo) - Roy Putra, Ferdiansyah; Annisa Nurizzati; Annisa Indah Pratiwi; Ahmad Said Haqiqi; Shinta Khairunnisa (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
The suboptimal distribution routes at PT. Baruna Globalindo have resulted in a significant increase in the company's operational costs. This study aims to design an optimal routing model for goods delivery using the transportation method in linear programming. Through this approach, it is expected to obtain an optimal solution that can minimize total transportation costs and improve operational efficiency. This study aims to compare the performance of the North West Corner (NWC) and Vogel's Approximation Method (VAM) in minimizing transportation costs. The analysis results show that the VAM consistently produces lower operational costs compared to the NWC method. In October 2024, the operational cost obtained using the NWC method was Rp.59,900, while the VAM method resulted in a cost of Rp.43,900. A similar trend was also observed in November 2024, with the NWC method's operational cost being Rp.66,100 and the VAM method being Rp.49,800. This comparative analysis offers a solution that companies can implement to enhance their goods distribution efficiency.